2004
DOI: 10.1111/j.1475-682x.2004.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Religious Homogeneity on the Rate of Divorce in the United States

Abstract: This study extends the understanding of the relationship between religious homogeneity, that is, the extent to which formal religious groups are concentrated at the county level, and the rate of persons currently divorced in those counties. Linking the research question to Durkheimian precepts of religion as an integrative force in social life, the essential question is, "At the county level, does the rate of currently divorced vary inversely with more concentrated affiliation with formal religious organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
1
8
1
Order By: Relevance
“…But although previous research indicates that this relationship holds when concentration indices are analyzed for all religious groups combined (Mullins et al, 2004), the current findings strongly suggest a different pattern when major religious categories are analyzed independently. The most obvious exception in the present case is the Jewish category.…”
Section: Summary and Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…But although previous research indicates that this relationship holds when concentration indices are analyzed for all religious groups combined (Mullins et al, 2004), the current findings strongly suggest a different pattern when major religious categories are analyzed independently. The most obvious exception in the present case is the Jewish category.…”
Section: Summary and Discussioncontrasting
confidence: 91%
“…Earlier research by the authors (Mullins et al, 2004) indicated that the higher the concentration score for all religious bodies combined, at the county level of analysis, the lower the rate of the currently divorced. Specifically, after controlling for the same covariates as those used in this study, the strength of the relationship between religious concentration and rate of divorce in the 2004 study was β = -.119.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Additionally, membership in a church is often an avenue to gain supportive networks for family members (Mahoney et al, 2001;Marks, 2004;McCubbin & McCubbin, 1988;Tanyi, 2006;Walsh, 1998). Data from a random sampling of 621 U.S. counties revealed that religious couples had lower divorce rates that couples without a religious faith (Mullins, Brackett, Bogie, & Pruett, 2004). Rew, Wong, and Sternglanz (2004) reported that children, regardless of ethnicity, who frequently prayed experienced higher levels of social connectedness and positive health behaviors than children who did not regularly pray.…”
Section: Spiritualitymentioning
confidence: 99%
“…We know too that participation in faith communities can provide coping mechanisms and has the potential to promote health and well‐being (Ellison 1991; Koenig, McCullough, and Larson 2001; Sherkat and Ellison 1999). Sociologists have also suggested that marital stability and harmony are related to religious participation and level of integration within a community (Ellison, Bartkowski, and Anderson 1999; Mullins et al 2004). Marital benefits result from therapeutic and counseling relationships, religious ideology and practice, network formation and social capital, and identification with community.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies addressing religion and divorce are based on quantitative analyses of large samples and are concerned with causal relationships. For example, scholars have explored the susceptibility of interfaith marriages to divorce, assessed divorce rates in denominations, correlated divorce with religious membership, analyzed the effects of religiosity and social networks on lifelong marriage, and measured differences in programming for divorced and single members (e.g., Amato et al 2007; Chiswick and Lehrer 1991; Mullins et al 2004; Stolzenberg, Blair‐Loy, and Waite 1995; Wilcox, Chaves, and Franz 2004). These are important questions, but their dominance in the literature hinders the development of a more comprehensive conversation that takes seriously questions about religious meaning and process as life partnerships end.…”
Section: Introductionmentioning
confidence: 99%